Genetic Improvement in Pongamia pinnata (Linn.) Pierre for Production of Bio-Fuel - Kumar, Ashok; Dobhal, Shivani; Savita, (Indian Forester, 2016)
Pongamia pinnata has become an extremely important tree species for extraction of oil for bio-diesel. The study conducted on various stages of storage revealed that the freshly harvested seeds produce maximum oil of 35.27%, which reduces substantially with storing duration. The seeds stored at 4Â° C for six months were found to have 33.34% oil. The same was further reduced when seeds were stored at temperature for six months to 32.49%. The oil content also varies from progeny to progeny and Progeny 81 was found to contain highest oil content of 41.43%. Therefore, utilization of seeds of such genotypes for bio-diesel could play significantly important role in bridging the gap between demand and supply.